Encylopedia of Indian philosophies; Vol V Philosophy of the Grammarians - Raja, K. Kunjunni K.; Coward, Harold G. (ed) (Delhi Motilal Banarsidas, 2006)
Introduction to the Philosophy of the Grammarians